Žydų lošimo vilkeliai Lietuvos archeologinėje medžiagoje - Blaževičius, Povilas (Archaeologia Lituana, 2005)
The article discusses and analyzes data of archaeological and historical sources concerning about a narrow and unique group of archaeological finds, a peculiar gaming dice variety, the so-called dreidl or sevivon. The paper covers the period of the 17th-20th centuries A.D. The most archaic form of dices is the so-called babkės (астрагалы (Rus.) or knucklebones (Eng.)). It is a tarsus bone of a sheep, goat or a horned animal (Fig. 1). For the purpose of games, these bones were used without any treatment. Gradually rectangular, cubical (Fig. 2) and top (Fig. 3) dices developed from these bones. Top-form dices where of several types. One of them, with six sides numbered from one to six. appeared in the Middle Ages. Another form of the top shape dices is a cube with an axis (Fig. 4). Four letters were marked on its four functional planes. They suggested what the player had to do. Such playing tops, so-called teetotum, were already known in Ancient Greece, and some scientists think that they came from an even earlier period in India. In the Middle Ages, playing tops became popular again. These teetotum tops evolved into so-called dreidls. On the four sides of teetotum tops, four Latin letters T, A, D, and N, were marked. They suggested what the player had to do. Later, the letters were replaced according to the country and the players of the game with a letter of the alphabet meaning a certain action. On the sides of the dreidl top there are four letters נ, ג, ה, ש. The fact that Hebrew letters on the sides of the dreidls are a mnemonic expression of the Yiddish language words corresponding to four actions of the teetotum game allows us to think that the spinning tops got into the Jewish culture through the Yiddish-speaking Ashkenazis. Facts allow us to affirm that dreidls, which has become a national Jewish game in our days, is undoubtedly taken from the Germans. It could have happened in about the 16th century A. D. The historical facts and data of archaeological science also provide interesting information about dreidls. Some of them were found during recent archaeological researches in Lithuania. All of them were found in urban cultural layers (Vilnius, Vilkija, Seredžius, Zapyškis, Kulautuva). According to the form they could be divided into three groups. The first, widely known, type of dreidls looks like a cube with an axis (Figs. 5, 6). The second type of dreidl is very similar to the first, the only difference being the lower part of the axis of the second type, which has a form of an overturned pyramid (Figs. 7, 8). The third type is totally different from the previous two. The dreidls are in a form of two square plane surfaces which cross at one axis. They look like small propellers with four paddles and have characters on both sides. Therefore, there are four characters, each repeated twice on such a dreidl. On both sides of the paddle, the same characters are inscribed (Fig. 9). Taking into account that the chronology of all dreidls is not exact, it is possible that these games reached Lithuania in about the 17th century. They spread widely in 18th-19th centuries, and the Jews use them until now. All of them were made from lead or its alloys. They are small, cube-shaped artifacts with the axe to spin them. Almost identical finds are known throughout Europe. Only the third type, four-edged dreidls, are unique. In the meantime, because of their unusual form, it is not known how these dreidls were used.